Penggunaan Multimedia Pada Materi Klasifikasi Zat Di Kelas VII SMP Negeri 1 Palu - Secsiolita, Raisa; Pursitasari, Indarini Dwi; Tiwow, Vanny M. A. (Jurnal Akademika Kimia, 2015)
This study was conducted to seek the use of instructional media multimedia-based to supportintegrated science learning especially on chemical materials. This instructional media was used to assistteachers in teaching of chemical materials to improve learning outcomes of students in the class VIIat the State Junior High School 1 Palu. The population in this study were 528 students class VII atthe State Junior High School 1 Palu. The sample in this study was 32 students of class VII M as anexperimental class and 33 students of class VII K as the control class. The results of the data analysisobtained an average value (Ï‡1) of experiment class was 84.96 with a standard deviation of 6.21 and theaverage value (Ï‡2)of control class was 82.16 with a standard deviation of 9.69. The results of hypothetictesting was tc = 4.137 and tt = 1.67 with a significance level Î± = 0.05. Based on the results it can beconcluded that the use of multimedia in the material of substance classification gave positive effect onthe learning outcomes of students in the Class VII at the State Junior High School 1 Palu.